Evaluation of cervical length and optimal timing for pregnancy after cervical conization in patients with cervical intraepithelial neoplasia: A retrospective study. Issue 49 (4th December 2020) - Zhang, Xiao; Tong, Jinfei; Ma, Xudong; Yu, Hailan; Guan, Xiaojing; Li, Jianqiong; Yang, Jianhua
Abstract : Abstract: To evaluate the change of cervical length and the best timing for pregnancy after cervical conization in patients with cervical intraepithelial neoplasia (CIN). This was a retrospective study including patients under 40 years with fertility desire treated by cervical conization for CIN. To assess the cervical length, the patients were divided into 2 groups according to different surgery procedure: loop electrosurgical excision procedure (LEEP) and cold knife conisation (CKC). Patients with cervical length < 2.5 cm in CKC group were divided into 2 groups according to whether receiving cervical cerclage. Trans-vaginal ultrasound examination was used to measure cervical length by fixed professional sonographers. In LEEP group, the cervical length preoperative was significantly longer than 3 months postoperatively (3.03 ± 0.45 cm vs 2.84 ± 0.44 cm, P  = .000). In CKC group, the cervical length preoperative was significantly longer than 3 and 6 months postoperatively (2.90 ± 0.41 cm vs 2.43 ± 0.43 cm and 2.68 ± 0.41 cm, respectively, P  = .000). Cervical length was significantly longer at 12 and 9 months after cerclage compared to that without cerclage. Eighteen patients got pregnant in LEEP group, among which one was pregnant at 5 months postoperatively and had premature delivery. There was 1 inevitable abortion and 1 preterm birth among 39 pregnant patients from CKC group. Patients who have fertility desire with CIN were recommended for pregnancy at 6 and 9 months after LEEP and CKC, respectively. Cerclage effectively prolonged cervical length in patents with that less than 2.5 cm to prevent cervical incompetence.